Cytotoxic Potential of Compounds Isolated from Non-Polar Fractions of Sungkai Plant Leaves (Peronema canescens Jack) Against Artemia salina Leach Larvae - Suryati; Irfan Afrinal; Afrizal; Rahmi Vika Ulia (Jurnal Riset Kimia, 2024)
The sungkai plant (Peronema canescens Jack), belonging to the Lamiaceae family, is a plant that is traditionally used as medicine, including toothache, malaria, and fever medicine. In this research, isolation was carried out with vacuum liquid chromatography (VLC), solid and liquid fractions were obtained. The solid fraction was further separated using column chromatography to obtain the isolated compound as a white solid (amorphous) weighing 10 mg (melting point 140˚C-142˚C). The results of the UV spectrum data show that there are no conjugated double bonds. The results of the IR spectrum show the presence of C-H groups at wave numbers 2921,49 cm-1 and 2856,94 cm-1, C=O groups at wave numbers, C=C groups at wave numbers 1641,51 cm-1, and dimethyl germinal which is characteristic of triterpenoid compounds at wave numbers 1456.68 cm-1 and 1372.41 cm-1. Meanwhile, the isolated oil was analyzed for chemical components using GC-MS. It was discovered that there were 83 chemical compound components contained therein with 4 main compound components, namely pentadecanoic acid (16.65%), 9,12-octadecanoic acid (16.12%), propyl palmitate (7.89%), and hexadecenoic acid, methyl ester (5.59%). A cytotoxic test was carried out on both fractions using the Brine Shrimp Lethality Test (BSLT) method. The results showed that the isolated compound was non-toxic with an LC50 value of 190214.2807 mg/L and the isolated oil was very toxic with an LC50 value of 34.2452 mg/L.